Tensions et résolutions : musicalité de l’intrigue ou intrigue musicale ? - Raphaël Baroni (Cahiers de Narratologie)
In his famous commentary of Sarrazine, Barthes argues that there is “the same constraint in the progressive order of the melody and in the narrative sequence, which is equally progressive”. Werner Wolf states meanwhile that “music can create suspense by disharmonious passages or excursions into foreign keys which before coming to harmonious resolutions or returning to the home key.” In these lines, we aim to show that if we agree to redefine the plot, not as the structure of the story told, but as a dynamic form that depends on a progression through phases of tension and resolution, it is no longer the main gap between narrative and music, but, on the contrary, one of the most obvious feature that they share.